Targeting the endo-lysosomal autophagy pathway to treat inflammatory bowel diseases. Issue 128 (April 2022) - Retnakumar, Sruthi Vijaya; Geesala, Ramasatyaveni; Bretin, Alexis; Tourneur-Marsille, Julien; Ogier-Denis, Eric; Maretzky, Thorsten; Nguyen, Hang Thi Thu; Muller, Sylviane
Abstract: Inflammatory bowel disease (IBD) is a serious public health problem in Western society with a continuing increase in incidence worldwide. Safe, targeted medicines for IBD are not yet available. Autophagy, a vital process implicated in normal cell homeostasis, provides a potential point of entry for the treatment of IBDs, as several autophagy-related genes are associated with IBD risk. We conducted a series of experiments in three distinct mouse models of colitis to test the effectiveness of therapeutic P140, a phosphopeptide that corrects autophagy dysfunctions in other autoimmune and inflammatory diseases. Colitis was experimentally induced in mice by administering dextran sodium sulfate and 2, 4, 6 trinitrobenzene sulfonic acid. Transgenic mice lacking both il-10 and iRhom2  − involved in tumor necrosis factor α secretion − were also used. In the three models investigated, P140 treatment attenuated the clinical and histological severity of colitis. Post-treatment, altered expression of several macroautophagy and chaperone-mediated autophagy markers, and of pro-inflammatory mediators was corrected. Our results demonstrate that therapeutic intervention with an autophagy modulator improves colitis in animal models. These findings highlight the potential of therapeutic peptide P140 for use in the treatment of IBD. Highlights: The risk of developing IBD is associated with polymorphisms in autophagy genes. We show that autophagy is altered in the colon and spleen of mice with colitis. The autophagy modulator P140 attenuated clinical disease in experimental colitis. Defective autophagy was restored after intravenous injection of P140 in mice. P140, which is safe in autoimmune patients, may be effective for treating IBD.